Using the microbiota to study connectivity at human–animal interfaces - Muloi, Dishon M.; Caron, Alexandre; Berkley, J.A.; Hassell, James M.; Brito, I.L.; King, K.; Moodley, Arshnee; Fèvre, Eric M. (Elsevier, 2025)
Interfaces between humans, livestock, and wildlife, mediated by the environment, are critical points for the transmission and emergence of infectious pathogens and call for leveraging the One Health approach to understanding disease transmission. Current research on pathogen transmission often focuses on single-pathogen systems, providing a limited understanding of the broader microbial interactions occurring at these interfaces. In this review, we make a case for the study of host-associated microbiota for understanding connectivity between host populations at human–animal interfaces. First, we emphasize the need to understand changes in microbiota composition dynamics from interspecies contact. Then, we explore the potential for microbiota monitoring at such interfaces as a predictive tool for infectious disease transmission and as an early-warning system to inform public health interventions. We discuss the methodological challenges and gaps in knowledge in analyzing microbiota composition dynamics, the functional meaning of these changes, and how to establish causality between microbiota changes and health outcomes. We posit that integrating microbiota science with social-ecological systems modeling is essential for advancing our ability to manage health risks and harness opportunities arising from interspecies interactions.